Analysis of Trade Relations between the European Union and Latin America from 1995-2011 - Daza Aramayo, Lourdes Gabriela, 1983-; Krebs, Vojtěch, 1950-; Macháček, Jaroslav; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2014)
The Doctoral Thesis "Analysis of Trade Relations between the European Union and Latin America from 1995-2011" focuses on the determination Latin America's potential as a trading partner for the European Union. It will be based on an analysis of the region's trade relationships between 1995 and 2011 through different econometric models and a macroeconomic analysis. It will make recommendations for improving economic relation policies with Latin America and the European Union as well as identify the sectors which could represent great potential for trade between both regions. The research is divided into seven chapters: The first chapter covers international trade theory; this part comprises the theoretical aspects directly related to international trade. The second chapter analyzes the macroeconomic features of Latin American countries and compares them with data from the European Union. A separate, detailed analysis of 17 Latin American countries was performed and the potential of each one to make their importance known to the world and define their geopolitical position is described. The third chapter details the trade policies of the European Union and Latin America. The fourth chapter discusses trade relations between Latin America and the European Union through a look at the trade agreements that have been signed between the European Union and Latin American countries and tries to identify possible causes of failures for agreements not signed. This chapter also studies the sectorial composition of trade between the two regions, emphasizing the asymmetry between these trades flows as they enter the countries studied. The fifth chapter, the heart of this research paper, analyzes the trade relations between the EU and Latin America through a gravity model, identifying the obstacles and barriers to international trade between the two regions.
The second part of this chapter discusses institutional factors, which, as a result of the conclusions from the gravity model explained earlier in the chapter, play an important role in international trade between Latin America and the European Union. This section contains a comparative analysis of the situation of the institutional factors in the 29 Latin American countries which were analyzed in the gravity model. This chapter also includes a trade simulation between the Czech Republic and Latin America with the institutional factors in Latin America showing a 10% improvement. In the sixth chapter, the competitiveness of 17 Latin American countries is calculated using the results of the barriers to international trade through a new method based on the comparison of indicators, ranked by dimension and according to the weight thereof for a period of time. The last chapter focuses on the identification of the variables determining foreign direct investment in Latin America, represented by 29 countries and over a period of time from 1995 to 2011. It considers variables traditionally not considered such as the number of patents registered, the tax rate and institutional factors, which have revealed important explanatory variables as well as those traditionally considered such as GDP, inflation, population, the share of GDP by sector, income level, etc. The last part of this research lists the conclusions reached and proposes recommendations for economic relations policy development between Latin America and the European Union.
Vedoucí práce: Vojtěch Krebs
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations